1998
DOI: 10.1139/z98-015
|View full text |Cite
|
Sign up to set email alerts
|

Perkinsus qugwadi sp.nov. (incertae sedis), a pathogenic protozoan parasite of Japanese scallops, Patinopecten yessoensis, cultured in British Columbia, Canada

Abstract: The pathogenic protozoan that has caused high mortalities among cultured Japanese scallops, Patinopecten yessoensis (introduced into British Columbia in 1983), is described as a new species, Perkinsus qugwadi. As in other species in the genus Perkinsus, vegetative multiplication occurred in the intercellular spaces and haemolymph sinuses of all organs of the host. Although the morphology of all developmental stages was similar to that of other Perkinsus spp., differences were observed in the ultrastructural mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 0 publications
5
63
0
3
Order By: Relevance
“…The softshell clam Perkinsus species appears to be unique in its ability to undergo both schizogeny and active zoosporulation in culture media (McLaughlin & Faisal, 1998a). Zoospores of P. marinus, P. atlanticus, and P. quqwadi possess similar morpho logical features (Perkins 1976;Azevedo, 1989;Azevedo et al, 1990;Blackbourn et al, 1998). Detailed mor phology of P. olseni zoospores has not been reported; however, zoosporulation studies produced biflagellated zoospores (Lester & Davis, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The softshell clam Perkinsus species appears to be unique in its ability to undergo both schizogeny and active zoosporulation in culture media (McLaughlin & Faisal, 1998a). Zoospores of P. marinus, P. atlanticus, and P. quqwadi possess similar morpho logical features (Perkins 1976;Azevedo, 1989;Azevedo et al, 1990;Blackbourn et al, 1998). Detailed mor phology of P. olseni zoospores has not been reported; however, zoosporulation studies produced biflagellated zoospores (Lester & Davis, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…This proposal is supported by mole cular evidence (Kotob et al, 1999a, b). Further, the abi lity of P. quqwadi to develop at temperatures below 20° C Blackbourn et al, 1998) et al, 1987;McLaughlin & Faisal, 1998b).…”
Section: Flagella Of P Chesapeakimentioning
confidence: 99%
See 1 more Smart Citation
“…belongs to a group of parasitic protozoa which infect mollusks worldwide, particularly bivalves. Since the first report of Perkinsus marinus infecting the American oyster Crassostrea virginica (Gmelin, 1791) in the Gulf of Mexico (Mackin et al, 1950), other species of the genus Perkinsus have been reported infecting several species of marine mollusks around the world (Lester and Davis, 1981;Azevedo, 1989;Blackbourn et al, 1998;Villalba et al, 2004;Choi and Park, 2010). In Brazil, Sabry et al (2009) recorded the first occurrence of Perkinsus sp.…”
Section: Introductionmentioning
confidence: 99%
“…P. marinus was the first species of the genus to be described and was reported as the causative agent of mortalities of Crassostrea virginica in the Gulf of Mexico (Mackin et al 1950). Since the synonymy between P. olseni and P. atlanticus (Goggin 1994, Robledo et al 1999a, Murrell et al 2002, Cremonte et al 2005) and between P. chesapeaki and P. andrewsi (Dungan et al 2002, Burreson et al 2005 has been described, the remaining species of the genus are P. qugwadi in Patinopecten yessoensis (Blackbourn et al 1998), Perkinsus mediterraneus in Ostrea edulis (Casas et al 2004), and P. honshuensis in Ruditapes philippinarum (Dungan et al 2006); recently, P. behaensis has been described in oysters from China (Moss et al 2008). However, Perkinsus spp.…”
Section: Introductionmentioning
confidence: 99%